2011
DOI: 10.1590/s0100-40422011000300006
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização espectroscópica multivariada do potencial antioxidante de vinhos

Abstract: Recebido em 31/3/10; aceito em 7/10/10; publicado na web em 26/1/11 MULTIVARIATE SPECTROSCOPIC CHARACTERIZATION OF ANTIOXIDANT POTENTIAL OF WINE. In this work the antioxidant capacity of red wine samples was characterized by conventional spectroscopic and chromatographic methodologies, regarding chemical parameters like color, total polyphenolic and resveratrol content, and antioxidant activity. Additionally, multivariate calibration models were developed to predict the antioxidant activity, using partial leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Antioxidant capacity is strongly linked to the phenolic content [5,14,15]. This activity is attributed mainly to resveratrol [16], vitamine C [17], and to the anthocyanins content [18].…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant capacity is strongly linked to the phenolic content [5,14,15]. This activity is attributed mainly to resveratrol [16], vitamine C [17], and to the anthocyanins content [18].…”
Section: Resultsmentioning
confidence: 99%
“…However positive correlation between antioxidant capacity and total phenol content (r 2 > 0.5) was found in dry red table wines produced in the region of Rio Grande do Sul [34]. Similarly, another study demonstrated the existence of a strong correlation (r 2 =0.99) between antioxidant activity and total polyphenols in red wine samples from Curitiba, Garibaldi and Campo Largo [54].…”
Section: Phenolic Composition Of the Wines And Its Antioxidant Activimentioning
confidence: 93%
“…Os metabólitos secundários escolhidos para serem determinados em S. amara foram os taninos, visto que esta classe de compostos é abundante e representativa na referida espécie, conforme verificado em triagem fitoquímica preliminar. Para sua quantificação, o método de Folin-Ciocalteu é amplamente empregado (FOLIN;CIOCALTEU, 1927;MONTEIRO et al, 2005;GALLICE et al, 2011 (LOPEZ et al, 2005;MONTEIRO et al, 2005), optou-se por sua escolha para determinar os taninos totais na casca do caule da matéria-prima vegetal.…”
Section: Introductionunclassified